Radiological, trace elemental and petrographic characterization of maiganga coal deposit of Northern benue trough, North-Eastern Nigeria / Kolo Matthew Tikpangi - Kolo , Matthew Tikpangi (2016)
To meet the increasing demand for power generation due to the rapid growing urbanization and industrialization, Nigeria-the most populated country of Africa, is reactivating her coal industry as supplementary energy source. Maiganga coal-field is one of the recently discovered coal deposits in northeast Nigeria that is receiving great attention from the investors and entrepreneurs of coal energy. The deposit is also a prime target for power generation by Nigerian government, yet little is known about the basic properties of the deposit. In this study, radiological, trace elemental and petrographic analyses were performed in coal samples from Maiganga coal-field in order to determine the intrinsic characteristics of the coal deposit, and to understand the environmental and human health challenges that may be associated with its exploitation and utilization. Radiological characterization of coal samples from Maiganga coal-field was done using a P-type coaxial HPGe gamma-ray detector, while the trace elemental concentrations was determined by using inductively coupled plasma-mass spectrometry (ICP-MS). Organic petrographic analysis was performed on polished coal blocks using a LEICA CTR 6000 Orthoplan microscope under monochromatic and ultraviolet light illumination. Proximate analysis was carried out on pulverized coal samples using Perkin Elmer Diamond Thermogravimetric-Differential Thermal Analyser (TG-DTA). The obtained results showed that mean activity concentrations of 226Ra, 232Th, and 40K in the analyzed coal samples were 8.0±3.5, 7.0±2.4 and 27.4±11.4 Bq kg-1 respectively. These values were found to be very low relative to the world average values of 20, 20, and 50 Bq kg-1 respectively, provided by the United Nations Scientific Committee on the Effects of Atomic Radiation. Calculated radiological hazard parameters were all below safety limits provided for environmental and human protection. Concentrations of trace elements were found to be low relative to the world average values for low rank coals. Estimated enrichment/depletion factor was found to be less than one, indicating that coals from Maiganga coal-field are depleted in trace elements including those that are potentially hazardous. The results of petrographic analyses revealed that among the three available maceral groups, vitrinite macerals dominated the studied coal samples with average percentage composition of 41.50%. Mean random vitrinite reflectance varies from 0.25 to 0.52%. This suggested thermally immature lignite to subbituminous coal rank. The studied coal samples were characterized by low ash yield (3.9 to 9.9 %), which justifies government’s expectations of good quality coal for power generation, and for industrial and domestic consumption. This study revealed that exploitation and utilization of coals from Maiganga coal-field for whatever purpose is therefore safe from the perspective of human health and environmental protection.